1983
DOI: 10.1093/oxfordjournals.jbchem.a134548
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of Peptidylarginine Deiminase from Rabbit Skeletal Muscle

Abstract: The preceding paper described the identification and some properties of peptidylarginine deiminase, which catalyzes the deimination of arginyl residues in protein, from rabbit skeletal muscle, kidney, brain, and lung. In the present work we purified peptidylarginine deiminase from rabbit skeletal muscle with a 16% yield by 7 steps. The purification involved ion-exchange chromatography on DEAE-Sephacel, gel filtration on Bio-Gel A-0.5 m, and affinity chromatography on soybean trypsin inhibitor-Sepharose 4B and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
1

Year Published

1987
1987
2017
2017

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 0 publications
4
33
1
Order By: Relevance
“…However, we did not observe any synthesis of NO when the synaptosomal preparation was incubated with 200 kLM NH4Cl. Furthermore, Na-benzoyl-L-arginine ethyl ester, a substrate for peptidyl-arginine deiminase (20), was not a substrate, and formamidine, an inhibitor of bacterial arginine deiminase (21), had no effect in the present study. On the basis of its NADPH dependence, we have suggested that the reaction in vascular endothelial cells is an oxygenation (9).…”
Section: Discussioncontrasting
confidence: 63%
“…However, we did not observe any synthesis of NO when the synaptosomal preparation was incubated with 200 kLM NH4Cl. Furthermore, Na-benzoyl-L-arginine ethyl ester, a substrate for peptidyl-arginine deiminase (20), was not a substrate, and formamidine, an inhibitor of bacterial arginine deiminase (21), had no effect in the present study. On the basis of its NADPH dependence, we have suggested that the reaction in vascular endothelial cells is an oxygenation (9).…”
Section: Discussioncontrasting
confidence: 63%
“…8 ) These properties were confirmed by this study showing the absolute requirements for calcium ion and dithiothreitol for the modification of contrapsin (Fig. 3).…”
Section: Discussionsupporting
confidence: 78%
“…To determine whether PAD2 was increased in the white matter tracts of heterozygous PD2 mice, we used a polyclonal antibody generated against whole muscle PAD2 (Takahara et al, 1983;Takahara et al, 1989) to stain mouse brain sections. The antibody labeled white matter tracts in the corpus callosum of both normal and PD2 mice, with a higher degree of labeling in the white matter tracts of the PD2 brain ( Fig.…”
Section: Expression Of Pad2 Protein In Pd2 Micementioning
confidence: 99%